The Legal Protection of Personal Data in Islamic Perspective - Suwondo, Denny (UNISSULA, 2023)
The protection of personal data is a public right that must be protected, even in Islam through the words of the Prophet Muhammad SAW, advocating peace by promoting attitudes of mutual respect, respect and love for fellow human beings. This attitude must be practiced among other religious communities, not only among Muslims. The research purposes to discuss specifically the regulation of personal data protection in Indonesia and personal data protection from an Islamic perspective. The type of research used in this research is normative juridical or library legal research or doctrinal legal research, namely legal research by examining library materials and secondary materials. In the view of the Islamic perspective regarding the protection of personal data is monitored as an endeavor to maintain the benefit of individuals and society in the use of information technology and can be considered as an implementation of the principle of benefit in Islam.